THE INTERPRETATION OF LOVE AND LOVE IN YASSAVI WISDOM - Bahronova Dilnora Alisher qizi (Journals Park Publishing, 2022)
This article contains Aymad Yassavi's proverbs about love and romance, as well as stories and narrations that reveal their essence. Different views on Yassavi’s rank of love are explained, and the description of divine love is interpreted as a precious power.
Keywords: Khoja Ahmad Yassavi; Ibrahim Adham; Shams Tabrizi